Sinkronisasi Digital: Analisis Integrasi E-planning dan E-budgeting dalam Peningkatan Sakip di Pemerintah Kota Surabaya - Selomita Purnama Sari; Rosalina Meysela Nurtriana; Indra Devian Lumban Gaol (Jurnal Manajemen Riset Inovasi, 2026)
Surabaya City Government achieved the AA predicate in the 2024 SAKIP evaluation, becoming the first city in Indonesia to reach this highest distinction. Behind this achievement, the mandatory transition to SIPD RI presents real structural obstacles: program nomenclature mismatch, double-entry burden at the OPD level, and the risk of planning-budgeting linearity distortion. This study employs a systematic documentary analysis approach grounded in Digital Era Governance (DEG) and Policy-Budget Linkage Theory. The documentary corpus consists of the Surabaya RKPD 2024–2025, APBD documents, SIPD RI regulations, and SAKIP evaluation reports from KemenPANRB. The findings reveal that the system locking mechanism and digital-based performance cascading form the primary institutional foundation of Surabaya's SAKIP quality, while the compliance cost of SIPD RI standardization remains an unresolved institutional barrier. The novelty of this study lies in its analysis of digital system transition governance in a high-digital-maturity local government-a perspective consistently absent from Indonesian public administration literature, which predominantly examines regions with low digital capacity.